دراسة تحليلية عن كتاب النحو من سلسلة تعليم اللغة العربية في تعليم القواعد ومهارات اللغة العربية: An Analytical Study of the Book on Grammar in the Arabic Language Teaching Series in Teaching Grammar and Teaching Arabic Language Skills - Ronny Mahmuddin; Zulfiah Sam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research aims to know and describe a good textbook in teaching Arabic language skills, taking into account the teaching of grammatical rules to non-native speakers. As for the type of this research, it is qualitative descriptive research using the office method by analytical study on a textbook